Sorting by Reversals and Transpositions with Proportion Restriction - Brito, Klairton Lima; Alexandrino, Alexsandro Oliveira; Oliveira, Andre Rodrigues; Dias, Ulisses; Dias, Zanoni (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
In the field of comparative genomics, one way of comparing two genomes is through the analysis of how they distinguish themselves based on a set of mutations called rearrangement events. When considering that genomes undergo diﬀerent types of rearrangements, it can be assumed that some events are more common than others. To model this assumption one can assign diﬀerent weights to diﬀerent events, where more common events tend to cost less than others. However, this approach, called weighted, does not guarantee that the rearrangement assumed to be the most frequent will be also the most frequently returned by proposed algorithms. To overcome this issue, we investigate a new problem where we seek the shortest sequence of rearrangement events able to transform one genome into the other, with a restriction regarding the proportion between the events returned. Here we consider two rearrangement events: reversal, that inverts the order and the orientation of the genes inside a segment of the genome, and transposition, that moves a segment of the genome to another position. We present an approximation algorithm applicable to any desired proportion, for both scenarios where the orientation of the genes is known or unknown. We also show an improved (asymptotic) approximation algorithm for the case where the gene orientation is known.